Extending PTR based breath analysis to real-time monitoring of reactive volatile organic compounds. Issue 24 (30th October 2019) - Pugliese, Giovanni; Trefz, Phillip; Brock, Beate; Schubert, Jochen K.; Miekisch, Wolfram
Abstract : Direct time resolved mass spectrometric monitoring of reactive exhaled nitrogen- and sulfur-containing volatile organic compounds (VOCs) related to metabolic processes, diseases and bacterial activity. Abstract : Reactive exhaled volatile organic compounds (VOCs) such as nitrogen- and sulfur-containing substances may be related to diseases, metabolic processes and bacterial activity. As these compounds may interact with any surface of the analytical system, time-resolved monitoring and reliable quantification is difficult. We describe a proton transfer reaction time-of-flight mass spectrometry (PTR-ToF-MS) based analytical method for direct breath-resolved monitoring of reactive compounds. Aliphatic amines were used as test substances. Matrix adapted gas standards were generated by means of a liquid calibration unit. Calibration conditions were adapted in terms of materials, temperature and equilibration time. PTR-ToF-MS conditions were optimized in terms of inlet materials, transfer line and drift tube temperature and drift tube reduced electric field ( E / N ). Optimized PTR conditions in combination with inert materials and high temperatures considerably reduced the interactions of compounds with the surfaces of the analytical system. Good linearity ( R 2 > 0.99, RSDs < 5%) with LODs between 0.15 ppbV and 1.23 ppbV and LOQs between 0.24 ppbV and 1.94 ppbV could be achieved. The method was then applied to breath-resolved monitoring of reactive compounds in 17 healthy subjects after high and low oral protein challenge. Exhaled concentrations of trimethylamine, indole, methanethiol, dimethylsulfide, acetone, 2-propanol, 2-butanone and phenol showed significant changes after protein intake. Methanethiol concentrations increased 6-fold within minutes after the protein intake. Optimization of methods and instrument design enabled reliable breath-resolved PTR-MS based analysis of exhaled reactive VOCs in the sub-ppbV range. Continuous in vivo monitoring of exhaled amines and sulphur containing compounds may provide novel non-invasive insight into endogenous and gut bacteria driven protein metabolism.